2019
DOI: 10.1155/2019/4568039
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates in Pharmacological Properties of Chitooligosaccharides

Abstract: Chemical structures derived from marine foods are highly diverse and pharmacologically promising. In particular, chitooligosaccharides (COS) present a safe pharmacokinetic profile and a great source of new bioactive polymers. This review describes the antioxidant, anti-inflammatory, and antidiabetic properties of COS from recent publications. Thus, COS constitute an effective agent against oxidative stress, cellular damage, and inflammatory pathogenesis. The mechanisms of action and targeted therapeutic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…Previous studies have shown the antimicrobial [21], anti-inflammatory [22], antitumoral [23], and antioxidant [24] activities of COSs, as well their potential use in Alzheimer disease [25]. More details on the biological properties and applications of COSs are described elsewhere [26,27]. Recently, COSs have been exploited in nanotechnology aiming to tackle microbial resistance [28], and also tumor imaging and therapy [29] and drug-delivery [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the antimicrobial [21], anti-inflammatory [22], antitumoral [23], and antioxidant [24] activities of COSs, as well their potential use in Alzheimer disease [25]. More details on the biological properties and applications of COSs are described elsewhere [26,27]. Recently, COSs have been exploited in nanotechnology aiming to tackle microbial resistance [28], and also tumor imaging and therapy [29] and drug-delivery [30].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory activities of different CHOS mixtures with various compositions obtained from diverse preparation methods have been reported using different assay systems, such as mouse models and various cell lines including murine RAW 264.7 macrophages, murine microglial cell line BV-2 , and human endothelial T84 cells [ 2 , 31 ]. To the best of our knowledge, this is the first report on the anti-inflammatory activity of CHOS on human monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The application of CAR-CHIOS complexes can result in the synergistic effect. CHIOS exhibit anti-oxidant, anti-inflammatory and anti-cancer activities [ 22 , 23 ], positively affect probiotic bacteria [ 24 ] and have antimicrobial activity [ 25 ]. Moreover, chitosan, from which CHIOS are produced by enzymatic or chemical hydrolysis is approved as a food additive and introduced in the European Pharmacopeia and the US National Formulary in 2008 and 2011, respectively.…”
Section: Introductionmentioning
confidence: 99%